Great Events: the Spanish case - Trifiletti, Emilia Giovanna (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The paper theme concerns on the urban and territorial transformations produced by the Great Events in reference to the implementation/transformation of the transports system during the events itself. For this reason, the article analyzes the results, both final that attended, of the transformations of the last fifteen years in Spain during this extraordinary events. n particular the paper analyzes five study-case in relationship to different Great Events: - Barcellona and the 1992 Olympic Games; - Seville and the 1992 Universal Exhibition; - Bilbao and the construction of Guggenheim Museum (architectural landmark) in 1997; - Valencia and the 2007 American’s Cup; - Saragozza and the 2008 Expo, where a new station of the High Speed Train has been realized. Spanish cities have known how to take advantage of the Great Events and in this way they have modified the identity of the whole country. Spain is not only endowed with new great architectural patrimony and with new models of city, but mainly he is endowed with a modern and efficient transport system (airports, ports, subways and roads).